(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article provides a comprehensive analysis of the importance of learning English in the modern globalized world. It examines the role of English in education, professional development, technology, and intercultural communication. Additionally, it explores the historical spread of English, its function as a global lingua franca, and its impact on personal growth and cognitive development. The paper also addresses the challenges faced by learners and suggests effective strategies for improving language proficiency. Overall, the article argues that mastering English is essential for individuals who seek to succeed in an increasingly interconnected and competitive global environment.